Implementation of the occupational health and safety management system model according to DSTU ISO 45001:2018: challenges and opportunities for transport enterprises - Olena Sorochynska; Oleksandr Melnichenko; Ivan Kulbovskyi; Igor Derehuz (Збірник наукових праць Державного університету інфраструктури та технологій: серія "Транспортні системи і технології")
The article examines the features of the implementation of the international standard DSTU ISO 45001:2018 "Occupational health and safety management system" specifically at transport enterprises. The focus is on specific challenges associated with a high level of production risks, the mobility of the working environment and the complexity of technological processes in the transport sector. The key problems of implementing the standard are analyzed, in particular, the insufficient level of staff awareness, the need to modernize existing safety systems and adapt to modern occupational safety requirements. The potential benefits of implementing ISO 45001:2018 are identified, including a reduction in the level of occupational injuries, increasing the effectiveness of risk management and strengthening the image of the enterprise. Practical recommendations are proposed for optimizing the process of implementing the standard, taking into account industry specifics.